Operating the diamond storage ring with reduced vertical emittance - Martin, I; Abbott, MG; Apollonio, M; Hickin, D; Bartolini, R (2013)
In a synchrotron radiation light source, a reduction in vertical emittance can potentially increase the source brightness, reduce the spot size for microfocus beam lines or increase the vertical transverse coherence of the photon beam. With this aim, the target vertical emittance for the Diamond storage ring has been recently reduced from 27 pm.rad to 8 pm.rad (0.3% coupling). In this paper we discuss the main impacts of this reduction, along with the steps that have been taken to stabilise the coupling at the new value. Copyright © 2013 by JACoW.